Active courts and menu contracts - Luca Anderlini; Leonardo Felli; Andrew Postlewaite (Center for Economic Studies and ifo Institute (CESifo), 2006)
We describe and analyze a contractual environment that allows a role for an active court. The model we analyze is the same as in Anderlini, Felli, and Postlewaite (2006). An active court can improve on the outcome that the parties would achieve without it. The institutional role of the court is to maximize the parties' welfare under a veil of ignorance. In Anderlini, Felli, and Postlewaite (2006) the possibility of menu contracts between the informed buyer and the uninformed seller is described but not analyzed. Here, we fully analyze this case. We find that if we maintain the assumption that one of the potential objects of trade is not contractible exante, the results of Anderlini, Felli, and Postlewaite (2006) survive intact. If however we let all widgets be contractible ex-ante, then multiple equilibria obtain. In this case the role for an active court is to ensure the inefficient pooling equilibria do not exist alongside the superior ones in which separation occurs.
Keywords: C79; D74; D89; K40; L14; 330